2018
DOI: 10.1007/s11033-018-4384-4
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular remodeling after the first myocardial infarction in association with LGALS-3 neighbouring variants rs2274273 and rs17128183 and its relative mRNA expression: a prospective study

Abstract: Post-infarct left ventricular remodeling (LVR) process increases the risk of heart failure (HF). Circulating galectin-3 has been associated with fibrosis, inflammation and cardiac dysfunction during the remodeling process after myocardial infarction (MI). The aims of this prospective case study were to investigate the association of potentially functional variants in the vicinity of LGALS-3 locus, rs2274273 and rs17128183 with maladaptive LVR and whether these variants could affect LGALS-3 mRNA expression in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 40 publications
0
7
0
6
Order By: Relevance
“…There are two single-nucleotide polymorphism (SNP) sites located at chromosome 14 in exon 3 of LGALS3 which are most common, marked as rs4644 and rs4652 variants. The variant of rs4644 + 191 C > A substitutes histidine to proline at residue 64, whereas the variant of rs4652 + 292 A > C changes threonine at residue 98 to proline [8]. The results of the study showed the bilateral roles of different variants of Gal-3 in different types of malignancies.…”
Section: Introductionmentioning
confidence: 80%
“…There are two single-nucleotide polymorphism (SNP) sites located at chromosome 14 in exon 3 of LGALS3 which are most common, marked as rs4644 and rs4652 variants. The variant of rs4644 + 191 C > A substitutes histidine to proline at residue 64, whereas the variant of rs4652 + 292 A > C changes threonine at residue 98 to proline [8]. The results of the study showed the bilateral roles of different variants of Gal-3 in different types of malignancies.…”
Section: Introductionmentioning
confidence: 80%
“…Djordjevic et al (42) found that SNP rs2274273 gene variant was associated with LGALS-3 mRNA levels of expression in atherosclerosis tissue of human carotid plaque. Also, Djordjevic et al (13) found that rs2274273 SNP was significantly associated with relative expression levels of LGALS-3 with left-ventricular maladaptive remodelling and HF occurring six months after MI. In contrast to wild type homozygote (CC), the carrier of the T allele with genotypes (CT+TT) had significantly higher relative LGALS-3 mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Gal-3 is a 32-to 35kD glycoprotein coded in chromosome 14 (14q22.3) by lectin galactoside binding soluble three genes (LGALS-3) and made up of 6 exons and five introns (12). Various variants of single nucleotides in LGALS-3 are found in exon 3 of chromosome 14 and influence its gene expression, such as; rs2274273, rs4644, and rs4652 (13).…”
Section: Introductionmentioning
confidence: 99%
“…As a whole, our data suggest that GAL3 cardiac reduction triggers compensatory GAL3 production which activates CD98 and alternative macrophage activation by a GAL3 feedback loop mechanism. GAL3/LGALS3 compensatory serum and tissue levels have been also related to dilated cardiomyopathy and myocarditis and very recently its release from the heart into the circulation has been proven [33][34][35][36] . Circulating LGALS3 levels may not be disease-specific, but probably reflect in general healing and fibrotic conditions 37 .…”
Section: Galectin-3: Inflammation Wound Repair and Heart Failurementioning
confidence: 99%